2006
DOI: 10.1007/s10967-006-0092-y
|View full text |Cite
|
Sign up to set email alerts
|

Uranium release from a natural rock under near-natural oxidizing conditions

Abstract: Understanding how uranium (U) moves through the soil and groundwater is essential to determine the effectiveness of cleanup technologies. Uranium release and transport in the subsurface under oxic conditions have been reported to be mostly dependent on sorption onto Fe/Mn-oxide and complex interactions with organic substances. Available information in the literature however presents evidence of U retardation by natural sands. The aim of this investigation was to characterize U dissolution from a uraninite-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…No carbon-14 or krypton-85 was detected in the monitoring well, suggesting preferential retention or volatilization during transit to the water table. Noubactep et al (2006) demonstrated that carbonate addition enhanced uranium solubilization, while pyrite addition slowed initial uranium solubilization. Silicon dioxide and other rock constituents were found to retard uranium transport.…”
Section: Radioactive Metalsmentioning
confidence: 98%
“…No carbon-14 or krypton-85 was detected in the monitoring well, suggesting preferential retention or volatilization during transit to the water table. Noubactep et al (2006) demonstrated that carbonate addition enhanced uranium solubilization, while pyrite addition slowed initial uranium solubilization. Silicon dioxide and other rock constituents were found to retard uranium transport.…”
Section: Radioactive Metalsmentioning
confidence: 98%
“…Furthermore, the objective was not to achieve any steady state (pseudo-equilibrium) but rather to compare contaminant solubilization under different conditions. Previous studies (e.g., Noubactep et al 2006) showed that while using essay tubes of about 20 mL capacity and tap water a leaching time of 14 days (336 hours) was sufficient to achieve reproducible leaching results in non-disturbed experiments. The suitability of this leaching time was verified in preliminary works by investigating the effect of material particle size on the extent of contaminant release from each material (including CuFeS 2 -next section).…”
Section: Rationale For Choice Of Leaching Timementioning
confidence: 99%
“…Previous studies (e.g., Noubactep et al 2006) showed that while using essay tubes of about 20 mL capacity and tap water a leaching time of 14 days (336 hours) was sufficient to achieve reproducible leaching results in non-disturbed experiments. In the present study no effort was done to accelerate mass transfer.…”
Section: Rationale For Choice Of Leaching Timementioning
confidence: 99%